Development of nutritional bars using cereals, Andean grains and squid protein concentrate - Omote Sibina, Juan Rodolfo (2022)
The extrusion process can be transferred to high Andean areas with the idea of generating value chains for the cultivation of Andean cereals and grains. An extruded product has been developed using cereals, Andean grains and pota protein concentrate (CPPo) to develop a nutritional bar that is well accepted by children from 5 to 10 years of age. The most acceptable product, qualified as a functional product, was made with 60.0% corn, 19.0% rice, 15.0% kiwicha and 6.0% CPPo, the main characteristic of which was the absence of pota odor and flavor. Subsequently, the nutritional bar was prepared using 57.5% of the extruded product and adding 27.5% sugar, 10.0% glucose and 5.0% grated coconut. In the proximal chemical composition of the nutritional bar, the content of proteins (9.56%), fats (3.10%), carbohydrates (79.49%), moisture (6.54%) and fiber (0.63%) are highlighted. The true digestibility (DV) and biological value (BV) of the nutritional bar protein were 90.53% and 94.54%, respectively. Microbiological tests met the requirements for human consumption. Finally, the acceptability of the nutritional bar was high in children (93%) and met the children's requirement for essential amino acids.